Life cycle assessment of organic light emitting diode display as emerging materials and technology. (1st November 2016) - Amasawa, Eri; Ihara, Tomohiko; Ohta, Takashi; Hanaki, Keisuke
Abstract: This study presents a life cycle assessment of an organic light emitting diode display for smartphones, in which our research concentrated on generating a life cycle inventory of specialty chemicals and a fabrication process in manufacturing scale. Previous studies to investigate the environmental impact of organic electronics have been limited to organic photovoltaic cells in a laboratory scale fabrication, which prevents understanding of the practical impact of organic electronics. In this study, we computed cradle-to-gate environmental impact of the most commonly used organic electronics today: active matrix organic light emitting diode (AMOLED) display for smartphones, through the formulation of new approaches to construct inventories for emerging materials and processes. The approaches for constructing inventories of chemicals and fabrication process involve manipulation of existing inventory with stoichiometry, and application of observed correlation between display area and production cost in the display industry. The environmental impact assessment results communicate that integration of detailed material flow improves data representation of the production of complex chemicals. Additionally, environmental impact per AMOLED display exhibited superiority in global warming potential, when compared with a previous study on a comparative size of liquid crystal display. Highlights: This study presents cradle-to-gate life cycle assessment of organic LED display for smartphones. It is the first detailed study on the mass production of organic LED display. Inventory formulation approach for specialty chemicals is introduced. Estimation procedure for fabrication process in manufacturing scale is introduced. The result showed superior environmental benefit in global warming potential relative to liquid crystal display.